The Influence of Instagram Social Media Marketing, E-WOM, and Co-Branding on Brand Switching Behavior from Other Shoe Brands to Aerostreet Shoes through Purchase Intention (Survey of Aerostreet Shoe Consumers in Kuningan Regency) - Harjadi, Dikdik; Gunawan, Wely Hadi; Wijaya, Tri Sukma Wijaya (International Journal Administration, Business & Organization, 2024)
This study aims to determine the direct and indirect influence of Instagram as social media marketing, electronic word of mouth and co-branding on brand switching behavior through purchasing interest in Aerostreet shoe products. Sample in this research were people who are consumers of Aerostreet shoes as many as 120 samples. questionnaire used as the research instrument containing statements and distributed via Google form. SEM AMOS ver. 23 used as data proccesed in this research. The results showed: Instagram social media marketing has a significant and positive impact on purchase intention. Electronic word of mouth has a positive and significant effect on purchase intention. Cobranding has a positive and significant effect on purchase intention. Purchase Intention has a positive effect on brand switching. Instagram social media marketing has no effect and insignificant on brand switching. Electronic word of mouth has no effect and insignificant on brand switching. Co-branding has no effect and insignificant on brand switching. Purchase Intention can mediate the influences of Instagram social media marketing on brand switchin. Purchase Intention can mediate the influences of electronic word of mouth on brand switching. Purchase Intention can mediate the impact of co-branding on brand switching.